2016
DOI: 10.1186/s12944-016-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for PCSK9 treatment in 734 Hypercholesterolemic patients referred to a regional cholesterol treatment center with LDL cholesterol ≥70 mg/dl despite maximal tolerated cholesterol lowering therapy

Abstract: BackgroundLDL cholesterol (LDLC) lowering has been revolutionized by PCSK9 inhibitors, Alirocumab (Praluent) and Evolocumab (Repatha), approved as adjuncts to maximally tolerated cholesterol lowering therapy in heterozygous (HeFH) or homozygous (HoFH) familial hypercholesterolemia, and/or clinical atherosclerotic cardiovascular disease (CVD) where LDLC lowering is insufficient.MethodsWe applied FDA and insurance eligibility criteria for PCSK9 inhibitor use in 734 hypercholesterolemic patients serially referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…After taking into account the rising CVD costs in the United States, projected by the AHA to be approximately $1 trillion by 2030, we have postulated that the cost to society with an estimated 50% CVD risk reduction with PCSK9 inhibitor therapy [6, 10, 11] would be in the middle of the range of societal costs for CVD [6]. Subsequently, in 103 hypercholesterolemic patients [7] (61 with previous CVD events, first CVD event at median age 55, median LDLC 139 mg/dL despite maximal tolerated cholesterol-lowering therapy), we estimated direct and indirect costs of CVD, cost of estimated next 10-year CVD events, and PCSK9 inhibitor costs to assess whether PCSK9 inhibitors would provide an incremental cost-effectiveness ratio [21] within a society willingness to pay threshold [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After taking into account the rising CVD costs in the United States, projected by the AHA to be approximately $1 trillion by 2030, we have postulated that the cost to society with an estimated 50% CVD risk reduction with PCSK9 inhibitor therapy [6, 10, 11] would be in the middle of the range of societal costs for CVD [6]. Subsequently, in 103 hypercholesterolemic patients [7] (61 with previous CVD events, first CVD event at median age 55, median LDLC 139 mg/dL despite maximal tolerated cholesterol-lowering therapy), we estimated direct and indirect costs of CVD, cost of estimated next 10-year CVD events, and PCSK9 inhibitor costs to assess whether PCSK9 inhibitors would provide an incremental cost-effectiveness ratio [21] within a society willingness to pay threshold [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have projected that an estimated 24 million Americans could be eligible for PCSK9 inhibitor therapy [6, 7]. Prior to commercialization, efficacy and safety of ALI and EVO in patients has been evaluated through randomized controlled clinical trials [812], which have stringent inclusion and exclusion criteria, creating a highly selective cohorts of study patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on eligibility for PCSK9 treatment in 734 hypercholesterolemic patients referred to a regional cholesterol center with LDLc ≥70 mg/dL despite maximally tolerated statin therapy, and based upon the FDA-and insurance-approved eligibility criteria, Glueck et al51 reported 50 patients approved by an insurance company for PCSK therapy. It is believed that insurance companies may be signing some agreement with pharmaceutical companies for value-based or performance-based sharing risks.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that even if the drug price of PCSK9 inhibitors could be covered by an annual $245 billion savings in prevented CVD events, the high price of PCSK9 inhibitors still poses a substantial economic burden to the U.S. healthcare system if only accounting for direct medical costs from avoided CVD. (24) Another study suggested these agents may not be cost-effective in patients with FH or ASCVD at current U.S. prices.…”
Section: Introductionmentioning
confidence: 99%